1989
DOI: 10.1111/j.1365-2958.1989.tb00143.x
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, expression and sequence analysis of the gene encoding the 120kD surface‐exposed protein of Rickettsia rickettsii

Abstract: Rickettsia rickettsii (R strain) genomic DNA was partially digested and cloned into the lambda expression vector gt11 generating a genomic clone bank. Transformant plaques were screened with antisera generated against the 120 kiloDalton protein of R. rickettsii to detect those phage expressing the recombinant protein. The gene encoding the 120 kD protein was localized to a 4.3 kilobase SphI-BamHI fragment from the recombinant phage and subcloned into pUC18 and pUC19. Full-length expression of the recombinant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
4

Year Published

1992
1992
2000
2000

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 29 publications
0
38
0
4
Order By: Relevance
“…Since IgG antibodies produced for protein in an early stage of infection and for carbohydrates are known to possess a low affinity, such antibodies carry a high specificity that causes cross-reaction with a very similar or identical antigenic structure (7,16). Gilmore et al (10,11) demonstrated the cross-reactivity of rOmp B between SFG and TG and confirmed the ompB gene homology by Southern blot analysis using the cloned DNA of R. rickettsii ompB. The sequencing of the R. japonica ompB gene revealed the existence in rOmp B of a portion consisting of some 50 putative amino acid residues identical to those in R. typhi (Yan, Y., Uchiyama, T., and Uchida, T., manuscript in preparation).…”
Section: Discussionmentioning
confidence: 99%
“…Since IgG antibodies produced for protein in an early stage of infection and for carbohydrates are known to possess a low affinity, such antibodies carry a high specificity that causes cross-reaction with a very similar or identical antigenic structure (7,16). Gilmore et al (10,11) demonstrated the cross-reactivity of rOmp B between SFG and TG and confirmed the ompB gene homology by Southern blot analysis using the cloned DNA of R. rickettsii ompB. The sequencing of the R. japonica ompB gene revealed the existence in rOmp B of a portion consisting of some 50 putative amino acid residues identical to those in R. typhi (Yan, Y., Uchiyama, T., and Uchida, T., manuscript in preparation).…”
Section: Discussionmentioning
confidence: 99%
“…Five genes have currently been cloned and sequenced: the genes encoding citrate synthase (62), ADP/ATP translocase (61), and three surface proteins of 17 (3), 120 (27), and 190 (2) kDa in R nickettsii. We have located three of them on our profiles.…”
Section: Discussionmentioning
confidence: 99%
“…An example of the former situation was found for the 120 kDa Rickettsia rickettsii OMP (Gilmore et al, 1989(Gilmore et al, , 1991, which contains enough DNA in the ORF to encode a deduced 168 kDa protein.…”
Section: Dr2 T K T N E I T F a L A A T S K T~o R T P E L K E O L K T mentioning
confidence: 99%